Comercio digital (e-commerce) aplicado a los negocios agropecuarios - Chocho Tapia, Victor Andres (2021)
This research addressed the topic Digital commerce (E-commerce) applied to agricultural businesses, because the benefit provided by this alternative is unknown, which had as its main objective, applying digital business models to generate viable methodologies in business and agricultural companies. For this reason, a methodology was proposed, where the use of different technological tools is detailed, through the exploratory method and the analytical-descriptive method, facilitating the creation of networks and digital platforms adapted to the agribusiness sector, as is the case of Facebook and Instagram, from the Pezlandia pet store. Likewise, it allowed to manage the management and design of ten digital advertising campaigns for the city of Loja, through videos and promotional images, reaching an audience between 18-65 years of age, where those most interested in the product and service offered were 18-24 year olds, appreciating more interaction on the social network Facebook as opposed to Instagram. For this reason, by analyzing the results, it was concluded that the creation of networks and digital platforms allowed greater reach, visibility and recognition of the brand, generating new customers and sales. Finally, it is worth emphasizing that responsibly managing the management of social networks is very important when positioning a new product or service in the market. This is because the users of these platforms have access to a lot of information where they can compare and identify quality and price in real time. Key words: E-Commerce, social networks, branding, advertising.